Strategic Management and Information Systems / An Integrated Approach: Second Edition - Robson Wendy (Financial Times - Pitman Publishing, 1997)
This book brings together currently dispersed or advanced material into a digestible and coherent framework for the whole discipline. Introduction, Acknowledgements, Introduction to Strategic Management, Strategic Management and Planning, Analytical Tools in Strategic Management, Information Systems Strategy Formulation, What are Management Information Systems?, Strategy Planning for Information Systems, The Information Systems Strategic Planning ''Toolkit'', Frameworks for Integrating IS Strategies with Business Strategies, Information Value and IS investment, IS and Business Competition and Organization, Information Systems Strategy Choices, IS Resource Management, IS Management and the IS Profession, Managing User-Controlled Computing, Selection and Acquisition, Responsible IS Management, Author and General Index.